THE EFEECTIVENESS OF PSYCHODRAMA TECHNIQUE TO INCREASE STUDENTS’ SELF-ACCEPTANCE - resya noor diani; Riesa Rismawati Siddik (Universitas Medan Area, 2017)
Self-acceptance refers to individual satisfaction or happiness with itself that is necessary for good mental health. Adolescence who can accept themselves and acknowledge their condition are free to take advantage of the condition. They also acknowledge their weaknesses without blaming themselves. The using of group counselling service with Psychodrama Technique is expected for making an individual to accept its own condition. This research aimsto test the effectiveness of Psychodrama Technique for improving student’s self-acceptance in 16 Junior High School Bandung (8th class). Research method use pre-experiment, which is One Group Pretest-Posttest Design. Data is gathered by using questionnaire as measuring instrument for self-acceptance. This instrument refers to Shepard’s aspect and Berger’s indicators. Total participants are 24 students (male: 10 persons and female: 14 persons). Data calculation analysis used descriptive statistics to see the increase of self-acceptance score and pre-test and post-test analysis. This research shows that Psychodrama Technique is effective to improve student’s self-acceptance.